A Konten TikTok Sebagai Media Pembelajaran Pendidikan Agama Islam Di SMP - Iffah, Izzatul; Supriadi, Udin; Fakhruddin, Agus (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
Learning media is used for the learning process, one of which is learning Islamic Religious Education in Schools. Various types of learning media can be used today due to technological developments. The learning media referred to is the use of TikTok content in learning Islamic Religious Education in schools. This research attempts to conceptually describe the use of TikTok content as a learning medium for Islamic religious education in junior high schools. A qualitative approach and qualitative descriptive methods were used in this research. The findings that the researchers obtained were that the characteristics of TikTok content were in accordance with Islamic Religious Education teaching materials from the aspects of simplicity, integration, color, texture, lines, emphasis, balance, shape and attractiveness. Stages of selecting content according to Islamic Religious Education teaching materials based on objectivity, learning program, program targets, technical quality. TikTok content is in accordance with teaching materials for Middle School Islamic Education, including 10 content for class VII PAI teaching materials, namely faith in Allah, honesty and istiqamah, taharah, congregational prayers, the life journey of the Prophet, faith in angels, Friday prayers, plural prayers and qasar, hijrah Rasulullah, Khulafaur Rasyidin. There are 11 contents for class VIII PAI teaching materials, namely Faith in the Book of Allah, alcohol, honest and just behavior, Sunnah prayers, prostration (sahwi, thanksgiving, prayer mat), Umayyad Dynasty, simple life, stories of 25 prophets and apostles, deeds to people old age, fasting, halal and haram food and drink. There are 5 contents for PAI class IX teaching material, namely the end of the world, procedures for aqiqah, sacrifice and slaughter, the entry of Islam in Indonesia, Qada and Qadar, Hajj and Umrah. The process of designing Islamic Religious Education Learning Media by utilizing TikTok content starts from planning, material development, presentation and evaluation.